Methodological Investigations Towards the Synthesis of Sesquiterpene-neolignans - Glen, James (2021)
Lignans and neolignans are a family of compounds from the illicium genus. These compounds are derived from the oxidative coupling of the phenolic compound, chavicol. Investigations into the medicinal benefits of this diverse family of compounds are ongoing with promise shown in the growth of neurons and the fight against neurodegenerative diseases. Sesquiterpene-neolignans, a subclass of this family of compounds also show enhanced activity in this therapeutic area. Efficient syntheses of these derivatives are a key topic of research being pursued to enable future structure activity relationship studies to be carried out. Investigations towards the synthesis of the sesquiterpene-neolignan, monoterpenylmagnolol, have been employed within this thesis. Chemistry successfully utilised in previous syntheses of neolignan derivatives was investigated for compatibility with synthesis of monoterpenylmagnolol. Attempted rhodium catalysed addition or aryl constituents to the conjugated enone, cryptone, yielded inconclusive results. This creates a need for further optimisation of this conjugate addition reaction. In conjunction with this, computational studies into the hypothesised biosynthetic pathway of caryolanemagnolol were implemented. This study validated the theorised phenolic trapping of the caryolane core through a secondary carbocation intermediate.